2017
DOI: 10.1136/gutjnl-2016-312569
|View full text |Cite
|
Sign up to set email alerts
|

Novel insight into the role of microbiota in colorectal surgery

Abstract: Recent literature undeniably supports the idea that the microbiota has a strong influence on the healing process of an intestinal anastomosis. Understanding the mechanisms by which the bacterial community of the gut influences intestinal healing could open the door for new preventive and therapeutic approaches. Among the different mechanisms, data have shown that the production of specific reactive oxygen species (ROS) and the activation of specific formyl peptide receptors (FPRs) regulate intestinal wound hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 102 publications
(89 reference statements)
0
64
0
Order By: Relevance
“…The gut microbiota is inhabited by hundreds of species of symbiotic microbes, which provides resistance against colonization and invasion of pathogens, modulates gut immunity, inhibits the inflammatory signaling pathways . Antibiotics or mechanical bowel preparation can damage the intestinal microbiota, impair barrier function and, paradoxically, increase the rate of bacterial translocation and infectious complications after surgery . Although overwhelming evidence shows that combination of antibiotics and mechanical bowel preparation effectively reduces SSI rate in colorectal surgery, the current review indicates a further reduction of SSI risk by 28% for the use of probiotics.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The gut microbiota is inhabited by hundreds of species of symbiotic microbes, which provides resistance against colonization and invasion of pathogens, modulates gut immunity, inhibits the inflammatory signaling pathways . Antibiotics or mechanical bowel preparation can damage the intestinal microbiota, impair barrier function and, paradoxically, increase the rate of bacterial translocation and infectious complications after surgery . Although overwhelming evidence shows that combination of antibiotics and mechanical bowel preparation effectively reduces SSI rate in colorectal surgery, the current review indicates a further reduction of SSI risk by 28% for the use of probiotics.…”
Section: Discussionmentioning
confidence: 89%
“…[61][62][63] Antibiotics or mechanical bowel preparation can damage the intestinal microbiota, impair barrier function and, paradoxically, increase the rate of bacterial translocation and infectious complications after surgery. 64,65 Although overwhelming evidence shows that combination of antibiotics and mechanical bowel preparation effectively reduces SSI rate in colorectal surgery, [66][67][68] the current review indicates a further reduction of SSI risk by 28% for the use of probiotics. Currently, it is difficult to comment on the mechanistic benefit of a prophylactic regimen using probiotics and there are a lot of factors to explore.…”
Section: Possible Mechanisms For Findingsmentioning
confidence: 85%
“…For example, a recent report from Leeds, United Kingdom, has emphasized the need to recalibrate antibiotic prophylaxis for colon surgery as ever more resistant Enterobactericiae are found to be responsible for surgical site infections (31). Perhaps the time has come for surgeons to “hold court” and forge the path forward for the rational design of intestinal antisepsis protocols based on new understanding of the evolving microbiology of the alimentary tract in response to surgery (32). …”
Section: Towards a New Eramentioning
confidence: 99%
“…In the same way, a recent clinical study by Gopalakrishnan et al revealed that the composition of the gut microbiota could affect the antitumorous responses to anti-PD-1 immunotherapy in patients with metastatic melanomas 26. Finally, gut microbiota has been recently linked to the occurrence of postoperative complications after colorectal surgery, especially AL 10 27. Bacterial induction of an oxidative stress, notably through the production of ROS and the activation of specific pathways regulating intestinal scarring, is also suspected to be involved in the genesis of these postoperative complications 12 28…”
Section: Introductionmentioning
confidence: 98%